Application of Real‐time Ultrasound Elastography for Discrimination of Low‐ and High‐grade Serous Ovarian Carcinoma. (1st February 2013) - Xie, Meng; Zhang, Xuyin; Zhan, Jia; Hua, Keqin
Abstract : Objectives: The purpose of this study was to evaluate real‐time qualitative ultrasound elastography as an adjunct to conventional sonography for discrimination of low‐ and high‐grade serous ovarian carcinoma. Methods: Eighty‐six patients suspected of having serous ovarian cancer on the basis of clinical and biochemical evaluations underwent transvaginal and transabdominal sonography and then elastography and later underwent surgery. Results: Histopathologic analysis revealed 64 serous ovarian carcinomas (74.4%): 39 (60.9%) high grade and 25 (39.1%) low grade. The mean elasticity score ± SD was statistically significantly higher for low‐grade lesions (3.40 ± 0.76) than high‐grade lesions (2.08 ± 0.58; P < .001). There was a trend for high‐grade lesions to be less stiff than low‐grade lesions due to rapidly developing necrosis; conversely, low‐grade lesions developed relatively slowly so that their solid areas were stiffer and less elastic. The median elasticity score for low‐grade lesions (based on a 4‐point scale used to grade cervical lymph nodes) was 4 (stiffest), and the score for high‐grade lesions was 2. When the score of 4 was used for diagnosis of low‐grade carcinoma, elastography had 56.0% sensitivity, 100% specificity, a 100% positive predictive value, a 78.0% negative predictive value, and 82.8% accuracy. When the score of 2 was used for the diagnosis of high‐grade carcinoma, elastography had 66.7% sensitivity, 84.0% specificity, an 86.7% positive predictive value, a 61.8% negative predictive value, and 73.4% accuracy. Conclusions: Our results suggest that ultrasound elastography could be helpful for discrimination of low‐ and high‐grade serous ovarian carcinoma. Low‐grade lesions are stiffer and not as elastic as high‐grade lesions.